2014
DOI: 10.4081/nhs.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

The decapod fauna (Axiidea, Anomura, Brachyura) from the Late Pleistocene of Trumbacà, Reggio Calabria (Calabria, southern Italy)

Abstract: -We report a rich faunal assemblage from the Tyrrhenian (Late Pleistocene) of Trumbacà, located in the southern area of Reggio Calabria (Calabria, southern Italy). The only brachyuran reported to date from this locality is Ranilia constricta (A. Milne Edwards, 1880) by Vazzana (2008

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The studied propodus has a shorter subsquare palm with upper and lower margins converging anteriorly with numerous raised crests interlaced each other like "scale fish", differing in outline and ornamentation from those of the similar fossil and extant Mediterranean species Dardanus arrosor (Herbst, 1796) having more elongate palm longer than high, with upper and lower margin almost parallel. Based upon the subsquare palm with upper and lower margins converging anteriorly the studied propodus is assigned to D. substriatus (A. Milne Edwards, 1861), previously reported from the Pliocene of Piedmont (Sismonda, 1846; A. Milne Edwards in Sismonda, 1861); Tuscany (Ristori, 1886;De Angeli et al, 2009); from the Early Pliocene (now Early Pleistocene, see Baldanza et al, 2013) of Umbria (Pasini & Garassino, 2010b); and from the Early Pleistocene of Calabria (Garassino et al, 2014). Due to the poor preservation of the shell, a systematic attribution of the hosting gastropod is impossible.…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…The studied propodus has a shorter subsquare palm with upper and lower margins converging anteriorly with numerous raised crests interlaced each other like "scale fish", differing in outline and ornamentation from those of the similar fossil and extant Mediterranean species Dardanus arrosor (Herbst, 1796) having more elongate palm longer than high, with upper and lower margin almost parallel. Based upon the subsquare palm with upper and lower margins converging anteriorly the studied propodus is assigned to D. substriatus (A. Milne Edwards, 1861), previously reported from the Pliocene of Piedmont (Sismonda, 1846; A. Milne Edwards in Sismonda, 1861); Tuscany (Ristori, 1886;De Angeli et al, 2009); from the Early Pliocene (now Early Pleistocene, see Baldanza et al, 2013) of Umbria (Pasini & Garassino, 2010b); and from the Early Pleistocene of Calabria (Garassino et al, 2014). Due to the poor preservation of the shell, a systematic attribution of the hosting gastropod is impossible.…”
Section: Methodsmentioning
confidence: 51%
“…The specimen is housed in the Museo di Storia Naturale dell'Accademia dei Fisiocritici, Siena (MUSNAF). For the higher-level classification we follow the recent arrangement proposed by De Grave et al, (2009 Included fossil species: see Schweitzer et al (2010); Garassino et al (2014). ld: 6 mm;li: 5 mm;lpa: 8 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous representatives of Paguristes have been described from the fossil record, from the Albian (late Early Cretaceous) onwards (see Fraaije et al, 2015, table 1), but nearly all of these are based exclusively on chelae, with the exception of two, namely a partial shield from the upper Pleistocene of southern Italy, referred to Paguristes cf. syrtensis de Saint Laurent, 1971, by Garassino et al (2014 and a specifically indeterminate form, Paguristes sp., from the lower Eocene of northern Italy (Beschin et al, 2016). A comparison with this specimen is not made here, because this species will be placed in a different genus (Fraaije et al, 2020).…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…Though poor preserved, the studied specimens have the narrow orbito-frontal margin, with one strong extraorbital spine on both margins of rostrum and the possible presence of one spine on both anterolateral margins. These characters allow us to compare the specimens to Lyreidus paronae Crema, 1895, already reported from the Tortonian (Miocene) of Sciolze and from the Langhian (Miocene) of S. Margherita (Torino, Piedmont) (Crema, 1895), the Pliocene of Orta San Giulio (Novara, Piedmont) , the early Pleistocene of Poggio I Sodi and Poggi Gialli (Sinalunga, Tuscany) (De Angeli et al, 2009;Baldanza et al, 2013Baldanza et al, , 2017 and Volterra (Pisa, Tuscany) (Pasini et al, 2014).…”
mentioning
confidence: 94%
“…This species was originally described by Crema (1895) from the late Pliocene (Piacenzian) of Bra (Piedmont). Garassino, Hyžný & Pasini in Baldanza et al (2013) reported this species from the early Pleistocene (late Gelasian-early Calabrian) of Poggio i Sodi (Siena, Tuscany) and later Pasini et al (2014) reported this species also from the early Pleistocene bathyal environment of Volterra (Pisa, Tuscany). Finally, De Angeli, Garassino & Pasini in Baldanza et al (2017) reported this species also from the early Pleistocene of Poggi Gialli (Sinalunga, Tuscany).…”
mentioning
confidence: 99%